Stocktaking Robots, Automatic Inventory, and 3D Product Maps: The Smart Warehouse Enabled by UHF-RFID Synthetic Aperture Localization Techniques - Gareis, Matthias; Parr, Andreas; Trabert, Johannes; Mehner, Tom; Vossiek, Martin; Carlowitz, Christian (IEEE Microwave Magazine, 2021)
In our age of global networks and the Internet of Things, communication and identification with a transponder tagged on goods and products have become increasingly important [1]. There is not only a need for the identification of the labeled objects but also for finding their exact positions in 3D space. Radio-frequency identification (RFID) offers both and is, in fact, already used in a vast field of applications, such as access control, goods logistics, indoor localization, automation, stocktaking, and many others [2]-[6]. Figure 1 illustrates a mobile robot platform for automatic inventory rounds that is used to acquire 3D product maps with ultrahigh-frequency (UHF)-RFID technolog
CRIS-Team Scopus Importer:2021-03-05